Fraud Pentagon Analysis In Detecting Fraudulent Financial Reporting Using Beneish M-Score Model (On Banking Companies Registered In Indonesia Stock Exchange (Bei) In 2014-2018) - Warseno Warseno; Sarah Nila Ayu (IJAcc, 2023)
This study aims to detect Fraudulent Financial Reporting as measured using the Beneish M-Score that occurred in banking companies listed on the Indonesia Stock Exchange in 2014-2018 using seven independent variables, namely Financial targets, External pressure, Financial stability, Ineffective monitoring, Rationalization, Capability and Arrogance. The research sample used was 140 of 28 banking companies listed on the Indonesia Stock Exchange in 2014-2018. The type of data used is secondary data in the form of financial reports and company annual reports. The analysis technique used in this study is multiple linear regression analysis where previously the data was tested using the classical assumption test consisting of a normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results of this study indicate that the external pressure variable is proxied by Leverage Ratio (LEV), Financial stability is proxied by Asset Changes (ACHANGE), Ineffective monitoring is proxied by the proportion of independent commissioners (IND), and Change in board of directors is proxied by changes in the position of the board of directors (DCHANGE) can detect fraudulent financial reporting. Meanwhile, the Financial Target variable which is proxied by Return On Assets (ROA), Razionalization which is proxied by External Auditor Change (AUDCHANGE) and Arrogance which is proxied by the Number of CEO Photos (CEOPIC) are unable to detect fraudulent financial reporting. Simultaneously all the variables in this study were able to detect fraudulent financial reporting